Is the world becoming a more risky place? Trends in disasters and vulnerability to them - Torsten Feldbrügge; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2002)
Numerous publications about disasters are implying that disaster vulnerability is growing. The main reasons given for this are growing populations, climate change and increasing poverty. However, maybe the current perception of vulnerability to disasters rests primarily on a perspective focusing on the present and neglecting long-term trends. Moreover, a changed understanding of the term disaster perhaps reflects a changed perception of its scope. An intention of this study is the examination of the hypothesis that vulnerability to disasters has increased. To accomplish this, clarification is needed about what is, and what determines vulnerability. As a concept, Vulnerability to disasters is relevant for a world that changes rapidly in technological and settlement structures. Vulnerability can be manifested at different levels of analysis, from the individual to the household to the region and state. Apart from this, vulnerability differs according to the type of disaster. Because of the problems involved with the availability of data, the empirical part of this study primarily examines trends at the aggregate country and global level. The results show that on the whole, the number of registered disasters is rising. The monetary value of damage is also increasing. And the results show that people in developing countries suffer the most from disasters. However, - more importantly - the number of disasterrelated deaths has declined and the mortality risk induced by disasters has declined as well in the last two decades. In these crude terms, the world does not seem to become a more risky place. Improved organizational response and emergency aid contribute to that positive development.
Keywords: 330; Resource /Energy Economics and Policy; Katastrophe; Staatskrise; Wirtschaftskrise; Sozialer Wandel; Risiko; Welt